Identification and Delineation of Turag River Basin Boundary Using Remote Sensing Techniques (Journal of Environmental Science and Natural Resources, 2015)
The objective of this study was to identify the Turag river basin boundary using remote sensing techniques. Aerial photographs and Topographic maps from Survey of Bangladesh have been used for this study. Various remote sensing data namely Landsat TM (Thematic Mapper) and Quick Bird have been also to support the analysis. Digital Elevation Model (DEM) and as well as the Global Position System (GPS) based ground truth information have been used for the verification of the analyzed results. The Turag river basin boundary has been delineated and length of the basin boundary is 197.79 km and the total area of the Turag river basin is 1160.48 sq-km. Remote sensing data was very useful for identification and delineation of Turag river basin boundary but further high resolution remote sensing data can improve the accuracy level. Moreover, different seasonal temporal data (dry and wet) are also required for achieving the convincing results. However the study showed that different type of remote sensing sensors data are also useful for this study.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22166 J. Environ. Sci. & Natural Resources, 7(1): 169-175 2014